Diet Pattern and Dyslipidemia Among Type II Diabetes Mellitus Patients Diagnosed More Tthan One Year Visiting Tribhuvan University Teaching Hospital - Niroula, Samiksha; Subba, Rama; Karkee, Aarem (Nepalese Medical Journal, 2021)
Introduction: Dyslipidemia is a risk factor for coronary artery disease, a leading cause of mortality in patients with type 2 diabetes mellitus. This study aims to study the dietary pattern and dyslipidemia of type 2 diabetes mellitus patients visiting Tribhuvan University Teaching Hospital. Materials and Methods: Quantitative study was done to find out the dietary pattern and dyslipidemia of type 2 diabetes mellitus patients visiting Tribhuvan University Teaching Hospital. Patients with type 2 diabetes mellitus diagnosed for more than one year were included in the study. Results: The percentage of dyslipidemia in type 2 diabetes mellitus was found to be 88.5%. Dyslipidemia was found to be significantly associated (p<0.05) with alcohol consumption, regular dietary management, sedentary behavior, waist-hip ratio, body mass index, glycated hemoglobin, and hypertension. Dyslipidemia was also found to be significantly associated (p<0.05) with the dietary habit (vegetarian and non-vegetarian), consumption of cereals and its product, consumption of fruits, consumption of fast foods and street foods, consumption of red meat, and consumption of oilseeds. Conclusions: This study indicates the importance of dietary awareness and lifestyle modification for the management of dyslipidemia among type 2 diabetes mellitus.